Non‐surgical treatment of peri‐implant mucositis and peri‐implantitis at zirconia implants: a prospective case series. (26th August 2015) - Schwarz, Frank; John, Gordon; Hegewald, Andrea; Becker, Jürgen
Abstract Objectives To assess the efficacy of non‐surgical therapy for the management of peri‐implant diseases at a two‐piece zirconium implant system. Material & Methods Thirty‐four patients with 45 implants participated in this study. Seventeen patients (24 implants) were diagnosed with peri‐implant mucositis and received mechanical debridement + local antiseptic therapy using chlorhexidine digluconate (MD + CXH), while 17 patients (21 implants) diagnosed with peri‐implantitis were assigned to Er:YAG laser therapy. In both groups, post‐operative maintenance care included supramucosal plaque removal and local pocket irrigation using CHX. The primary endpoint was defined as disease resolution at 6 months (i.e. absence of bleeding upon probing (BOP) at mucositis sites/absence of BOP and probing pocket depths (PD) ≥6 mm at peri‐implantitis sites). Results Resolution of peri‐implant mucositis and peri‐implantitis was obtained in 9/17 (52.9%) (p = 0.001) and 5/17 (29.4%) (p = 0.02) of the patients respectively. Conclusion Non‐surgical treatment of either peri‐implant mucositis using MD + CHX or peri‐implantitis using ERL at zirconia implants was associated with significant short‐term clinical improvements. A complete disease resolution, however, was not achieved in the majority of the patients.